Development and improvement of tensile Split Hopkinson pressure bars testing with sheet specimen - Soh, Ren Haur. (2010)
Split Hopkinson pressure bar (SHPB) experimental testing method can be categories into compression, tension and torsion. SHPB testing is used to investigate the mechanical property of different material under high strain rate at compression, tension or torsion condition.